Investigation of the droplet dispersion influence on the atomization of liquid fuel processes in view of large-scale structures formation - Bolegenova, S.; Askarova, A.; Ospanova, Sh.; Slavinskaya, N.; Aldiyarova, A.; Zhagaparov, A.; Yerbosynov, D. (Recent Contributions to Physics, 2022)
This paper is devoted to an important research from the point of view of modern combustion physics of the problem of numerical modeling of spraying, ignition and combustion of liquid fuel at different values of the initial radius of the droplets. The need for a detailed study of the physicochemical processes taking place in the combustion of liquid fuels is determined by the increased requirements for the efficiency of various technical devices, the accuracy of the prediction of ignition, the burning rate and is because of modern environmental requirements for environmental protection. The efficiency of various technical devices, in particular internal combustion engines, is largely based on the results of a fundamental study of the processes of physics and combustion chemistry. Purpose of the work is to use methods of mathematical modeling, investigate the process of atomization, ignition and combustion of liquid fuel droplets at various initial radii, in the presence of turbulence, chemical transformations, and determine the optimal parameters for liquid fuel combustion. Computer simulation of the spray and combustion of liquid fuel injection was carried out using differential equations describing turbulent flow in the presence of chemical reactions. The theoretical significance of the research is that the fundamental results, which are got in this work, can be applied in the combustion’s construction theory to achieve a deeper understanding of complex physical and chemical phenomena, something in the combustion chambers. The practical significance of computational experiments is that the results obtained can be used in the design of various technical devices using combustion, which would solve simultaneously the problem of process optimization, increasing the efficiency of fuel combustion and minimizing emissions of harmful substances.